Estudo da eficácia de espuma para a depopulação de aves para situações de emergência sanitaria - Ishizuka, Masaio Mizuno; Ishizuka, Walter Kazuhiko; Buchala, Fernando Gomes; de Albuquerque, Ricardo; Matushima, Eliana Reiko; Andreatti Filho, Raphael Lucio [UNESP] (My University, 2011)
There are several difficulties in the control of quick spreading and highly contagious poultry diseases such as avian influenza and Newcastle disease, which require large numbers of poultry to be rapidly killed inside the poultry houses in order to minimize human exposure and disease spreading. We have built and tested an equipment that uses a waterbased foam from high expansion fire detergent that induces poultry anoxia measured by sensorial signs, time to death, lethality and macro and microscopically lesions. Two hundred 78-weeks old hens were divided into ten groups and exposed to different times of death according to exposure to water-foam varying from 5min30s to 8min15s. All poultry died after six minutes of water-foam cover. Foam bubbles were observed in oral cavity and trachea of all poultry at each time of exposure to foam, revealing physical asphyxia. Macroscopically, congestion in oral cavity and in trachea mucosa was observed. Histopathology revealed diffuse and moderate hemorrhage in lungs and no lesion in trachea. The efficacy of water-foam procedure for poultry depopulation was demonstrated validating its recommendation in case of emergency.
Experimental evaluation of foam-based poultry depopulation for emergencies
Keywords: Avian influenza; Depopulation; Foam; Mechanical hypoxia; Poultry; Aves